An asymmetric group key agreement protocol based on attribute threshold for Internet of Things. Issue 5 (25th November 2020) - Gan, Yong; Wang, Bingli; Zhuang, Yuan; Gao, Yuan; Li, Zhigang; Zhang, Qikun
Abstract: With the development of wireless mobile network and Internet of Things (IoT), users enter the network with a large amount of data and information, including some important personal information, such as ID number, telephone number. Personal privacy disclosure has become one of the focuses of attention. In this article, we propose an asymmetric group key agreement (GKA) protocol based on attribute threshold for IoT to protect user privacy. Users do not need to expose any personal information in the group, but only need to meet the same number of attributes and conduct bidirectional authentication registration with key generation center (KGC) to ensure the legitimacy of mobile terminal members participating in GKA. In the registration phase, user performs heavy preliminary calculations according to the designed protocol, thereby reducing the computation in the key agreement phase and decreasing the complexity of the protocol. The protocol can realize self‐verification, and any member participating in key agreement can verify the correctness of the negotiated key by themselves. Under the assumption of bilinear computational Diffie‐Hellman problem, the security of the protocol is proved. Performance analysis further shows that our protocol has lower energy consumption in terms of communication and computing. Abstract : In this article, we proposed a protocol that terminals only need to meet the same number of attributes without any personal information and conduct bidirectional authentication registration with key generation center (KGC), ensuring the legitimacy of mobile terminal members participating in group key agreement. The protocol can realize self‐verification so that any member participating can self‐verify the correctness of the negotiated key. The performance analysis shows our protocol has lower energy consumption in terms of communication and computing.